Lumbar instrumented posterolateral fusion in spondylolisthetic and failed back patients: a long-term follow-up study spanning 11–13 years - Turunen, Veli (Springer-Verlag, 2012)
INTRODUCTION AND MATERIALS: We examined lumbar transpedicular instrumented posterolateral fusion patients operated on between 1992 and 1997 presenting: degenerative spondylolisthesis with spinal stenosis; adult isthmic spondylolisthesis; failed back syndrome after one to five discectomies; and failed back syndrome after one to three laminectomy operations (Groups 1–4, respectively). METHODS: They were examined by an independent orthopedic surgeon, completed the Oswestry Disability Index (ODI) and visual analog scale (VAS) questionnaires and their outcome was evaluated. RESULTS: The overall patient satisfaction at follow-up (mean 11.7 years) was 82.1 %. The reoperation rate was 15.1 % (7.5 % due to adjacent segment disease). CONCLUSION: Group 1 showed the greatest improvements in ODI and VAS values, Group 2 the lowest and Group 3 the highest preoperative values, and Group 4 the second highest improvements. Patient satisfaction scores were 90.3, 69.7, 63.6 and 80.0 %, respectively, and unplanned reoperation rates were 6.5, 9.1, 31.8 and 20.0 %. Thus, long-term outcomes of lumbar instrumented posterolateral fusion (rarely previously studied) were satisfactory for >80 % of patients, but varied among groups.